Factors predicting health-related quality of life following necrotizing fasciitis. Issue 6 (June 2018) - Gawaziuk, J.P.; Strazar, R.; Cristall, N.; Logsetty, S.
Summary: Background: Necrotizing fasciitis (NF) is a debilitating soft tissue infection that results in disfiguring scars and often amputations. While mortality rates have improved, long-term outcomes in survivors of NF are poorly understood. Objectives: The objective of this study is to analyze the impact of NF on survivors' health-related quality of life (HRQoL) influenced by age, sex, comorbidities, %TBSA, and confidence with appearance. Methods: We surveyed 56 adult patients with NF treated at either of two regional referral centers in Manitoba, Canada, between January 1, 2004, and December 31, 2014. Necrotizing soft tissue infections involving the fascial planes were identified during surgical debridement. HRQoL was measured by the Medical Outcomes Short Form-36. Derriford Appearance Scale-24, age, sex, comorbidities, and %TBSA were recorded, and group comparisons and stepwise regression models were developed for the mental and physical component scores separately. Results: Mean Mental Component Score (MCS) was 44.5 ± 14.3 and mean Physical Component Score (PCS) was 36.5 ± 11.5; both means were lower than the Canadian population norm of 50. Although stepwise linear regression analyses with block entry indicated influence from age, sex, and comorbid conditions for the MCS and PCS, the only factors that were statistically significant in the final models were confidence with appearance for the MCS and %TBSA for the PCS. Conclusions: NF has long-term impact on mental and physical health-related quality of life. Distress regarding confidence with appearance affects mental quality of life, whereas the size of the injured area impacted physical quality of life. These findings can help guide targeted interventions that could potentially improve recovery from NF.